Educational Media Leaflet Increases Nurses' Knowledge about Nursing Documentation Audit - Hasrianti, Raden Sri; Patima; Amal, Andi Adriana; Rauf, Syamsiah (Bantayang Omni Cendekia, 2024)
Background: The nursing management process starts with planning, organizing, commanding/coordinating, and controlling. One part of the controlling function is the nursing documentation audit. Nursing documentation audit is a professional evaluation process on the quality of nursing services which have been carried out by the nursing and midwifery profession against patients, namely through patient medical records. Objective: Nurses can implement nursing documentation audits at Ar-Raudah 1 room of Makassar Hajj Hospital. Methods: This study used a case study method. This study implemented education through leaflet media to enhance nurses' knowledge in implementing nursing documentation audits. A total of 14 nurses participated in this study. Data collection was obtained from interviews, observations and questionnaires. Results: The findings showed that the pre-test nurses' knowledge on P3 as many as 10 nurses (71.4%) answered correctly and as many as 4 nurses (28.6%) answered incorrectly. As for P7, 14 nurses (100%) answered incorrect. An increase in knowledge occurred during the post test, namely P3 (100%) and P7 (100%). After nursing implementation, namely education through leaflet media, it showed that nurses' knowledge increased in the application of nursing documentation audits. Conclusion: Nurses at Ar-Raudah 1 room of Makassar Hajj Hospital show an increase knowledge about nursing documentation audits.